The Effectiveness of Attachment-Based, Brain-Based, and Mindful Parenting Training on Parental Stress in Children with Symptoms of Social Anxiety - Karimi, Hossein; Latifi, Zohreh; Yousefi , Zahra (Applied Family Therapy Journal (AFTJ), 2024)
Objective: This study aimed to evaluate the effectiveness of attachment-based, brain-based, and mindful parenting training on reducing parental stress in mothers of children exhibiting symptoms of social anxiety. Methods: A quasi-experimental design with a pre-test, post-test, and follow-up stages was used, involving 60 mothers from three elementary schools in Felard city. Participants were divided into four groups: attachment-based parenting, brain-based parenting, mindful parenting, and a control group. Each experimental group received eight 90-minute training sessions. Parental stress was measured using the Parenting Stress Index before and after the intervention and during follow-up. Data were analysed using SPSS-26 and analysis of variance with repeated measurements method. Findings: The brain-based parenting training significantly reduced parental stress in the post-test and follow-up stages compared to the control group. The attachment-based and mindful parenting trainings did not show significant effects on parental stress. Repeated measures ANOVA indicated significant within-group effects over time and interactions between time and group. The brain-based training had a notable impact on the mothers’ ability to manage parenting stress effectively. Conclusion: Brain-based parenting training is an effective intervention for reducing parental stress among mothers of children with social anxiety symptoms. The findings highlight the importance of understanding brain functions in parenting strategies. Further research is needed to explore the potential long-term benefits of attachment-based and mindful parenting methods on parental stress.